A latest Pliocene age for the earliest and most extensive Cordilleran Ice Sheet in northwestern Canada - Hidy,AJ; Gosse,JC; Froese,DG; Bond,JD; Rood,DH (Quaternary Science Reviews, 2013)
The Klondike gravel is a widespread glaciofluvial gravel marking the earliest and most extensive Cordilleran Ice Sheet (CIS) in NW North America. New terrestrial cosmogenic nuclide (TCN) burial ages indicate this gravel was emplaced 2.64+0.20/-0.18 Ma (1σ). Coupled with previously interpreted paleomagnetic stratigraphy, this numerical age constrains the timing of the earliest CIS to the late Gauss Chron and provides a minimum age for the Upper White Channel gravel, a significant placer gold source in the Yukon. This implies the first CIS glacial maximum pre-dates the maximum extent of the Laurentide Ice Sheet, indicating that during the initial stages of northern hemisphere glaciation, the most extensive glaciers were present in the relatively cold and high elevation northern Cordillera. Our results verify the CIS as a likely source of persistent coeval ice-rafted debris in the northern Pacific, and suggest that the first CIS formed as a response to the establishment of the northern Pacific halocline and emergence of the 41 ka obliquity cycle during the Plio-Pliocene transition. © 2012 Elsevier Ltd.